Bid rigging : an analysis of corruption in auctions - Yvan Lengwiler; Elmar Wolfstetter (Center for Economic Studies and ifo Institute (CESifo), 2005)
In many auctions, the auctioneer is an agent of the seller. This invites corruption. We propose a model of corruption in which the auctioneer orchestrates bid rigging by inviting a bidder to either lower or raise his bid, whichever is more profitable. We characterize equilibrium bidding in first- and second-price auctions, show how corruption distorts the allocation, and why both the auctioneer and bidders may have a vested interest in maintaining corruption. Bid rigging is initiated by the auctioneer after bids have been submitted in order to minimize illegal contact and to realize the maximum gain from corruption.
Keywords: D44; 330; auctions; procurement; corruption; right of first refusal; numerical methods; Auktionstheorie; Korruption; Theorie